MAKING SUBALTANITY: THE LUNCH LADIES IN THE DOCUMENTS AND INITIATIVES OF THE FEDERAL ADMINISTRATION OF THE PNAE - Melgaço, Mariana Belloni (2021)
This paper deals with the lunch lady (Merendeira), a professional responsible for preparing school meals in Brazilian public schools and who plays a key role in achieving the goals of the National School Meals Program (PNAE): to contribute to the biopsychosocial growth and development, learning, school performance and the formation of healthy eating habits of students. Despite the importance of the lunch lady for the program, her educational potential is often invisible and unrecognized in the school environment. Because of this, this study aimed to investigate what are the documents and initiatives developed by the federal management of PNAE that involve the lunch lady and if they can contribute to the (de)valorization of her profession and her maintenance as a subject that does not participate in the decisions in the school environment, reinforcing her subaltern position. The document analysis allowed to verify that the program has a legal framework to strengthen and enhance the roles of the lunch ladies, especially concerning the role of educator. However, the analysis suggests that the actions are more focused on the scope of registration in the official discourse than on representation/representation, which can contribute to their social discredit and the consolidation of their role as a subordinate subject.